Immunohistochemical evaluation of CD25+ cell expression in the progression of periodontal disease - Lins,Ruthinéia Diogénes Alves Uchoa (2012)
It was assessed the immunohistochemical profile of CD25+ cells in cases of chronic gingivitis (CG) and chronic periodontitis (CP). Immunohistochemistry was carried out using streptoavidin-biotin complex and anti-CD25 antibody in 17 cases of CG and 25 cases of CP. Sixteen cases (94.1%) of CG were immunopositive. CD25 was focally expressed in 50% of the sample and diffusely expressed in 25%. The stained cells were localized not only beneath the epithelium, but also far from it. In relation to the cellular density quantification of CD25+ cells, score ++ was the most common. Concerning CP, all cases were immunopositive. CD25+ cells were expressed in focal or diffuse pattern either close or far from the epithelium. Diffuse distribution of positive cells throughout the connective tissue was seen in 60% of the cases and 32% showed focal or diffuse cellular pattern. Sixteen cases (64%) received score +++. It was identified that CD25+ cells are present in either a focal or a diffuse pattern in connective tissue. Significant differences in the density of cellular immunostaining between CG and CP were found. The greatest density was observed in CP cases, which suggests that the infiltrate of lymphocytes show a higher degree of cellular activation in periodontitis compared with gingivitis.